Peningkatan Motivasi Belajar Siswa Melalui Pendekatan Permainan dalam Pembelajaran Penjas - Panjaitan, Kristianto; Fardana, Nurainy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to increase students' motivation by implementing learning innovations through a game approach in Physical Education Learning. This is expected to make lessons more attractive and students more active and enjoyable. This research uses the integrative Systematic Literature method, where researchers review and identify journals in a structured manner in each process by following predetermined steps. From various articles, the researcher chose ten articles that were closely related to the keywords used. After reviewing ten articles, it was found that the game approach in sports learning can motivate students to participate in knowledge. In conclusion, providing games in sports learning is a form of teacher innovation in increasing motivation and learning achievement. Keywords: Games, motivation to learn